JAIPONGAN CIPTANING FEELING BOJONGAN - Agus Dian; Tati Narawati; Tatang Taryana (Universitas Pendidikan Indonesia, 2023)
Jaipongan dance is one of the arts which is still developing in West Java. The Jaipongan dance takes several folk-dance elements from the Priangan and Kaleran regions. One of the figures who is still preserving, developing, and continuing the jaipongan dance is the figure of Lalan Ramlan. The jaipongan Ciptaningrasa Bojongan dance by Lalan Ramlan is a dance that has a dynamic, energetic, masculine character and this dance aims to preserve and develop so that pair dances (opposite sex) are kept alive, especially for male dances. The purpose of this research is that the researcher aims to examine and find out some information on the ideas of working on dance construction in the creation of the Jaipong Ciptaningrasa Bojongan Dance by Lalan Ramlan. The research method used is a descriptive qualitative method of analysis with an ethnochoreological approach. This method is used to solve and explain the idea of working on, choreography, make-up, and clothing regarding the Jaipongan Ciptaningrasa Bojongan Dance. Data collection was carried out by researchers through observation, literature studies, interviews, and documentation. The results obtained in this study were able to study and analyze the choreographic form of the Jaipongan Ciptaningrasa Bojongan Dance in an ethnochoreological approach. As for the movement structure uses pure movement, gesture (Gesture movement), locomotion (moving places), and baton signal (expression booster) with the structure of the jaipongan dance (bubuka, nibakeun, pencungan, mincid), it can be concluded that the Jaipongan dance Ciptaningrasa Bojongan is a dance with a new presentation style starting from the form of movement choreography, music choreography and the form of the make-up arrangement without losing the aesthetic value of the previous jaipongan dance.